Concepts and Methods for the Study of Chinese Religions, Volume I, State of the Field and Disciplinary Approaches - Laliberté, André; Travagnin, Stefania (De Gruyter, 2019)
The three-volume project 'Concepts and Methods for the Study of Chinese Religions' presents a history of the study of Chinese religions. It evaluates the current state of scholarship, discusses a variety of analytical approaches and theories about methodology, epistemology, and the ontology of the field. The three books display an interdisciplinary approach and offer debates that transcend national traditions. It engages with a variety of methodologies for the study of East Asian religions and promotes dialogues with Western and Chinese voices. This volume covers successive historical stages in the study of religion in modern China, draws out the genealogy of major figures and intellectual achievements in a variety of research traditions, and highlights as well the challenges and evolutions experienced by the main disciplines in the last 30 years. This volume serves as a reference for graduate students and scholars interested by religions in modern Chinese societies (i.e., mainland China, Taiwan, Hong Kong and Chinese communities oversea). Using a wide range of methods, from textual analysis to fieldwork, it presents case studies via the disciplines of religious studies, anthropology, sociology, history, and political science
Description based on online resource; title from PDF title page (publisher's Web site, viewed 28. Aug 2019)
Keywords: Anthropologie; anthropology of religion in China; China; History of Chinese religions; political science and religion in China; Religionsgeschichte; sociology of religion in China; Soziologie; LITERARY CRITICISM / Asian / General; Religion -- Methodology; Religion -- Research; Theology -- Research